TRANSLATION SHIFT FROM ENGLISH INTO INDONESIA ON THE BAD GUYS SUBTITLING - Sulaiman, Salma R; Sama, Gratiana; Doi, Maksimilianus; Ngatu, Simon P K (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
This study aims at explore the types of translation shifts in the subtitles of the movie The Bad Guys. This research is based on Catford's theory of shifts and utilizes a qualitative descriptive method. The data collected involves translations found in the dialogues of the characters Wolf, Snake, and Diane Foxington, focusing on words, phrases, clauses, and sentences that contain shifts. The results show that all types of shifts are found in the translated text of the movie